Labour Flexibility and Migration in the EU Eastward Enlargement Context : The Case of the Baltic States - Tiiu Paas; Raul Eamets; Marit R??m; Rena Selliov; Anne Jürgenson; Jaan Masso (Free University Berlin, Jean Monnet Centre of Excellence, 2002)
The eastward enlargement of the European Union and the requirements of the European Monetary Union increase pressure for flexibility of labour markets. This paper analyses main changes in the Baltic States? labour market over the period 1990 - 2001 giving emphasis on the problems of labour market flexibility and migration in the EU eastward enlargement context. Labour market flexibility issues are analysed paying attention to wage flexibility and institutional flexibility (regulations, labour policy, trade unions) while labour migration problems are discussed giving emphasis on pull and push factors of migration and on labour migration experience during the previous stages of EU enlargement. In conclusion labour market flexibility is relatively high in all three Baltic States, being a bit higher in Estonia and lower in Lithuania. In all three states the flexibility has declined in the course of transition. The weakness of the trade unions compared to EU has contributed to the high wage flexibility, while the insufficient funding of labour policies and high share of passive measures might have had negative effect on flexibility. Labour migration from the Baltic States into the EU15 countries will not be significant in the near future. Still the free movement of labour will have pressure on the labour markets of the Baltic States due to possible movement of better-qualified and flexible labour force and due to possible crossborder movement of workers in the Baltic Sea region.
Keywords: J50; J30; J21; J80; J61; H50; 330; Labour market flexibility; labour migration; Baltic States; eastward enlargement of the European Union; Arbeitsmarktflexibilisierung; Internationale Arbeitsmobilität; EU-Erweiterung; Nordosteuropa; EU-Staaten